Human-computer interface glove using flexible piezoelectric sensors - Cha, Youngsu; Seo, Jeonggyu; Kim, Jun-Sik; Park, Jung-Min (IOP PUBLISHING LTD, 2017)
In this note, we propose a human-computer interface glove based on flexible piezoelectric sensors. We select polyvinylidene fluoride as the piezoelectric material for the sensors because of advantages such as a steady piezoelectric characteristic and good flexibility. The sensors are installed in a fabric glove by means of pockets and Velcro bands. We detect changes in the angles of the finger joints from the outputs of the sensors, and use them for controlling a virtual hand that is utilized in virtual object manipulation. To assess the sensing ability of the piezoelectric sensors, we compare the processed angles from the sensor outputs with the real angles from a camera recoding. With good agreement between the processed and real angles, we successfully demonstrate the user interaction system with the virtual hand and interface glove based on the flexible piezoelectric sensors, for four hand motions: fist clenching, pinching, touching, and grasping.
Keywords: MOTION